Pengaruh Pemahaman Perpajakan, Sistem Perpajakan, dan Sanksi Pajak Terhadap Persepsi Mahasiswa Mengenai Penggelapan Pajak - Elya Rozana Usman; Yudea; Dika Karlinda Sari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to find out the influence of tax understanding, tax system, and tax sanctions on students' perception of tax evasion. The number of samples used in this study was 166 students of the accounting study program at the University of Balikpapan. Sampling in this study used non-probability sampling using the purposiv method. The analysis method used is the Partial Least Square-Structure Equation Model (PLS-SEM). The results of this study show that the understanding of taxation, the tax system, and tax sanctions affect students' perception of tax evasion